"A Blessing on Our People": Bibi Pak Daman, Sacred Geography, and the Construction of the Nationalized Sacred. (July 2014) - Zaidi, Noor
Abstract This article focuses on the hagiographies and debates related to Bibi Pak Daman, a small shrine in Lahore's Old City. Said to house the graves of six women from the Prophet Muhammad's household and subject to a range of theories regarding its origins, Bibi Pak Daman is critical space in validating Pakistan's religious character and centrality in broader map of Islam. The most widely disseminated claim maintains that the main mausoleum in Bibi Pak Daman is that of Bibi Ruqayyah bint Ali, daughter of ῾Ali ibn Abu Talib, the fourth of the "Rightly Guided" Caliphs and the first Shiite Imam. The implications of this presence allow devotees to link Bibi Pak Daman to seminal events in the formation of Islamic and Shiite history in particular, affirming that the lands that would become Pakistan were vital at Islam's inception, rather than a much later, peripheral recipient of Muhammad's message. Yet like no other site in Pakistan, Bibi Pak Daman exemplifies the tensions that exist between state sanctioned religious rhetoric and local and folk traditions, with the unease with the government's role as religious arbitrator, between nationalism and communal rivalry, and within a minority Shiite community often struggling to legitimate its beliefs in a nation with a rapidly‐narrowing space for public religious plurality.